1987
DOI: 10.1063/1.452077
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact excitation cross section studies of methane and acetylene

Abstract: We have measured the electron impact emission cross sections for CH4 and C2H2 at 200 eV in a crossed beam laboratory system. Included in the study are all vacuum ultraviolet (VUV) emission features from 40 to 200 nm. The features are entirely from the atomic dissociation fragments (C i, C ii, and H). The Lyman series of H is observed to truncate near principal quantum number n=10 due to the long lifetime and to the high kinetic energy of the excited H fragments. The threshold region of the excitation functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…Beside Lyman-α and -β emissions, Pang et al [13] reported also the observation of CI emissions at 165.7 nm and measured the threshold energies.…”
Section: →Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside Lyman-α and -β emissions, Pang et al [13] reported also the observation of CI emissions at 165.7 nm and measured the threshold energies.…”
Section: →Xmentioning
confidence: 99%
“…A comparison could only be made with the results of the dissociative excitation experiments of C 2 H 2 giving rise to CI(3s, 1 P) emission at 193.1 nm [12] and 165.72 nm [13]. The onset for CI(3s, Table 1).…”
Section: Straight Line (5) Inmentioning
confidence: 99%
“…In contrast to photo-excitation, electron impact implies also optically forbidden excited states and monitors their subsequent decay to lower states. Pang et al investigated electron impact emission cross sections for CH 4 and C 2 H 2 in the VUV region from 40 to 200 nm [17]. Three studies are most related to the present study since electrons were used as projectiles and fluorescence signals in the VIS/UV range were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the broad field of applications for studies on methane an extended number of previous experimental investigations on electron ionization (see [13,14]), electron attachment [15,16] and dissociative electron impact excitation can be found in the literature for this molecule [17][18][19][20]. Emission spectra for electron projectiles [11][12][13][14] as well as for photo-excitation [21][22][23] were reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation